Force : character design from life drawing - Mattesi, Michael D. (Burlington, MA ; Oxford, UK : Focal Press, 2008)
Design creative characters inspired by real people. Let Mike Mattesi show you how to use life drawing to discover the poses, features and personalities which form the basis of character and then build, develop and 'PUSH' your drawings to new heights of dramatic and visual impact for believable characters audiences can relate to. Packed with color illustrations and photographs of the models who inspired them. With step-by-step explanation of how the characters were developed and exercises for you to sharpen your skills this is everything you need to bring your characters to life. * Push your character designs to the next level with creative life drawing * See how it's done; with photographs of models and the characters they inspired * Unlock your imagination; put the theory into practice with detailed exercises to sharpen your skills.
-- Introduction -- Force -- Form -- Shape -- Clothes -- Reportage -- Animals -- Glossary
Includes bibliographical references (pages 235-236) and index.
Keywords: Figure drawing -- Technique; Motion in art; Force and energy -- Miscellanea